Persepsi Mahasiswa Pendidikan Biologi terhadap Praktikum Online dan Perbandingannya dengan Praktikum Tatap Muka - Purwanti, Elly; Prihanta, Wahyu; Fauzi, Ahmad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2021)
The COVID-19 pandemic forced lectures to be shifted to online-based learning, including the implementation of practical activities. The purpose of this research is to examine the perception between students who take online practicum with face-to-face practicum. The research was conducted at the University of Muhammadiyah Malang, involving students of the Biology Education Study Program who had participated in environmental biology practicum. Data was collected using an open survey, using the google form. The survey results show that students feel that online practicum activities are not able to optimally facilitate the empowerment of their competencies.